Student-Centered Learning to Prevent Radicalization at Islamic Junior Schools in Surakarta Indonesia - Waston; Mahmudulhassan; Andri Nirwana; Muthoifin; Ishmah Afiyah; Nuha (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
Youth radicalization presents serious threats to the peace and stability of society, particularly in educational environments. The purpose of this study is to investigate how Student-Centered Learning (SCL) at Islamic Junior Schools functions as a deterrent to radicalization. Critical thinking, inclusivity, and active student involvement are all promoted by SCL and are essential in lowering a person's vulnerability to extreme views. This study investigates the use of SCL in promoting an inclusive learning environment through a qualitative method that includes teacher and student interviews. The results show that SCL encourages critical thinking and respect for one another, assisting students in interacting with a range of perspectives and fending off extreme influences. However, obstacles including insufficient training for teachers and a lack of resources prevent SCL from reaching its full potential in counter-radicalization initiatives. To optimize the effectiveness of SCL as a preventive measure against radicalization, the study emphasizes the necessity of professional growth and institutional support. Educational officials and organizations hoping to establish more secure and welcoming learning environments should take note of these findings.